Hubungan Antara Father Involvement Dengan Self-Esteem Pada Remaja - Yunanto, Kezia Prima; Kristinawati, Wahyuni (Innovative: Journal Of Social Science Research, 2025)
Penelitian ini bertujuan mengetahui hubungan antara father involvement dengan self-esteem pada remaja. Remaja merupakan masa krusial dalam pembentukan identitas diri, di mana peran orang tua, terutama ayah, sangat penting. Pendekatan kuantitatif dengan metode korelasional digunakan dalam penelitian ini. Sampel terdiri dari 137 remaja usia 15—18 tahun dari dua sekolah kejuruan di Salatiga, dipilih dengan teknik cluster sampling. Data dikumpulkan menggunakan dua skala: Inventory of Father Involvement (IFI) dan Rosenberg Self-Esteem Scale (RSES). Analisis menggunakan uji Spearman’s Rho menunjukkan adanya hubungan positif signifikan antara father involvement dan self-esteem remaja (r = 0.322; p < 0.001). Semakin tinggi father involvement, semakin tinggi pula self-esteem remaja. Hasil ini menegaskan pentingnya keterlibatan ayah dalam pengasuhan untuk mendukung perkembangan psikologis remaja. Implikasi penelitian ini diharapkan dapat meningkatkan kesadaran orang tua, pendidik, dan masyarakat akan pentingnya peran emosional dan pengasuhan ayah dalam masa tumbuh kembang anak.     Abstract This study aims to determine the relationship between father involvement and self-esteem in adolescents. Adolescence is a crucial period in the formation of self-identity, where the role of parents, especially fathers, is very important. A quantitative approach with correlational methods was used in this study. The sample consisted of 137 adolescents aged 15-18 years from two vocational schools in Salatiga, selected using cluster sampling technique. Data were collected using two scales: the Inventory of Father Involvement (IFI) and the Rosenberg Self-Esteem Scale (RSES). Analysis using Spearman's Rho test showed a significant positive relationship between father involvement and adolescent self-esteem (r = 0.322; p < 0.001). The higher the father involvement, the higher the adolescent self-esteem. This result confirms the importance of father involvement in parenting to support adolescents' psychological development. The implication of this study is expected to increase the awareness of parents, educators, and the community of the importance of the emotional and nurturing role of fathers in the growth and development of children.